Zhuriheng pills improve adipose tissue dysfunction and inflammation by modulating PPARγ to stabilize atherosclerotic plaques - Zhai, Qiong; Liang, Fangyuan; Yang, Guanlin; Liu, Zhimin; Dong, Xin; Bu, Ren; Xue, Peifeng; Na, Shengsang; Zhang, Xuan; Zhao, Pengwei; Wang, Xiaoning; Wei, Qiang; et al. (Frontiers in Pharmacology, 2025)
BackgroundAdipose tissue dysfunction and chronic inflammation contribute to atherosclerosis plaque development. Zhuriheng pills (ZRH) are an effective Mongolian herbal formula used in treating coronary heart disease in China, but their mechanisms of action have not been fully elucidated.PurposeTo assess whether ZRH alleviates atherosclerosis (AS) and stabilizes plaque, this study investigates the modulatory effects of ZRH on AS and adipose tissue profiles in atherosclerotic model mice with vulnerable plaque to reveal the potential mechanisms and representative quality markers (Q-markers) of ZRH.MethodsIn vivo, the vulnerable atherosclerotic plaque model was induced in ApoE−/− mice treated with intense co-stimulation. The anti-AS effect of ZRH was assessed by serum lipid profile, hematoxylin–eosin (HE), Oil O Red, Masson staining, immunohistochemistry (IHC), immunofluorescence, and plasma lipidomics. In vitro, a co-culture model was established with 3T3-L1 adipocytes treated with palmitic acid (PA) and RAW264.7 macrophages treated with lipopolysaccharide (LPS). The potential mechanism and Q-markers of ZRH were identified by lipid content test, inflammatory factors and adipocytokine analysis, flow cytometry for macrophage polarization, and Western blotting for PPARγ and UCP-1 proteins.ResultsIn vivo, ZRH stabilizes plaques by improving serum lipid profiles, lowering macrophage infiltration, and boosting collagen content in plaques. ZRH can counteract HFD-induced adipocyte hypertrophy, increase UCP-1 and PPARγ expression, enhance the “browning” of adipose tissue, and inhibit macrophage M1 polarization. Lipidomics results showed that ZRH treatment increased the abundance of lipid species with multiple unsaturated bonds and decreased harmful TAG, DAG, and HexCer. In addition, ZRH regulates inflammatory factors and adipokines in co-culture to inhibit macrophage M1 polarization and adipocyte abnormal lipid metabolism. In contrast, RDK and its monomers have a stronger anti-inflammatory effect, whereas GZ and its monomers regulate lipid metabolism better. ZRH was shown to be a PPARγ agonist for improving adipose tissue dysfunction and inflammation for anti-AS effects of ZRH. MIX, which comprises ellagic acid (G3), quercetin (G8), 3,3′-Di-O-methylellagic acid (G9), elemicin (R5), and safrole (R8) in equal proportions, is only one of ZRH’s Q-markers. More research is needed on the roles of different ZRH metabolites.ConclusionOur results demonstrated that ZRH stabilizes atherosclerotic plaques by ameliorating adipose tissue dysfunction and inflammation by regulating the PPARγ pathway.